YANTIMICROBIAL EFFECT OF CRUDE FROG (RANA RIDIBUNDA) SKIN SECRETIONS EXTRACT ON WOUNDS HEALING IN MICE - & et al., AL-Khafaji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Amphibians cutaneous glands spread over the skin which contain different bioactive substances. So, the aim of this study is to study the effects of frog skin secretions on parasites and pathogenic bacterial isolates. Five adult frogs (Rana ridibunda) from AL-Jadria streams in Baghdad used in this study. The frogs were stimulated by single intraperitoneal injection of norepinephrine-HCl (40ng/gm) body weight. Frogs skin glands secreted bioactive substances then washed .The washing solution was centrifuged, lyophilized and re-suspended and sterilized. The  result  of  the study  revealed that the concentration (500mg/ml) inhibited bacterial growth so as Staphylococcus aureus, Bacillus subtilis,  Escherichia coli, Pseudomonas aeruginosa and Fungi so as Candida albicans, while the concentration (250mg/ml) inhibited the growth of Salmonella  typhi. All concentrations of crude extract were cytotoxic for both of Leishmania  tropica and Leishmania  donovani cell culture by the evidence of significant regression and correlation (P